Association between pre-existing cardiovascular disease, mortality and cardiovascular outcomes in hospitalised patients with COVID-19 - Sritharan, Hari P.; Bhatia, Kunwardeep S.; van Gaal, William; Kritharides, Leonard; Chow, Clara K.; Bhindi, Ravinay (Frontiers in Cardiovascular Medicine, 2023)
Background Pre-existing cardiovascular disease and cardiovascular risk factors are common in patients with COVID-19 and there remain concerns for poorer in-hospital outcomes in this cohort. We aimed to analyse the relationship between pre-existing cardiovascular disease, mortality and cardiovascular outcomes in patients hospitalised with COVID-19 in a prospective, multicentre observational study. Method This prospective, multicentre observational study included consecutive patients of age ≥18 in their index hospitalisation with laboratory-proven COVID-19 in Australia. Patients with suspected but not laboratory-proven COVID-19 and patients with no available past medical history were excluded. The primary exposure was pre-existing cardiovascular disease, defined as a composite of coronary artery disease, heart failure or cardiomyopathy, atrial fibrillation or flutter, severe valvular disease, peripheral arterial disease and stroke or transient ischaemic attack. The primary outcome was in-hospital mortality. Secondary outcomes were clinical cardiovascular complications (new onset atrial fibrillation or flutter, high-grade atrioventricular block, sustained ventricular tachycardia, new heart failure or cardiomyopathy, pericarditis, myocarditis or myopericarditis, pulmonary embolism and cardiac arrest) and myocardial injury. Results 1,567 patients (mean age 60.7 (±20.5) years and 837 (53.4%) male) were included. Overall, 398 (25.4%) patients had pre-existing cardiovascular disease, 176 patients (11.2%) died, 75 (5.7%) had clinical cardiovascular complications and 345 (37.8%) had myocardial injury. Patients with pre-existing cardiovascular disease had significantly increased in-hospital mortality (aOR: 1.76 95% CI: 1.21–2.55, p = 0.003) and myocardial injury (aOR: 3.27, 95% CI: 2.23–4.79, p < 0.001). There was no significant association between pre-existing cardiovascular disease and in-hospital clinical cardiovascular complications (aOR: 1.10, 95% CI: 0.58–2.09, p = 0.766). On mediation analysis, the indirect effect and Sobel test were significant (p < 0.001), indicating that the relationship between pre-existing cardiovascular disease and in-hospital mortality was partially mediated by myocardial injury. Apart from age, other cardiovascular risk factors such as diabetes, hypercholesterolemia and hypertension had no significant impact on mortality, clinical cardiovascular complications or myocardial injury. Conclusions Pre-existing cardiovascular disease is associated with significantly higher mortality in patients hospitalised with COVID-19. This relationship may be partly explained by increased risk of myocardial injury among patients with pre-existing cardiovascular disease which in turn is a marker associated with higher mortality.